Efektifitas Nugget Tempe Sebagai Makanan Tambahan Untuk Menjaga Gizi Seimbang Pada Masyarakat Gunung Medan - Rati Purwati purwati; Evin Noviana Sari; Ita Dwiaini; Hafiza (Kreativasi : Journal of Community Empowerment, 2022)
This counseling aims to inform, remind, and provide education to the public regarding information and knowledge about the importance of maintaining balanced nutrition and how to do it. In this extension, tempeh nuggets will be the main object as one of the nutritional supplements which will be discussed during the counseling about what is contained in it and how to make it. To convey this counseling material using language that is easy to understand so that it is easily understood by the target of counseling. The media used in this counseling is print media. The conclusion of this activity is counseling about the importance of maintaining balanced nutrition to the community by suggesting nutritional supplements to help maintain balanced nutrition in a more enjoyable way. Based on the results of this study, many parents are interested in making this food as a snack for additional nutrition for their family.